Elastomeric Cardiowrap Scaffolds Functionalized with Mesenchymal Stem Cells-Derived Exosomes Induce a Positive Modulation in the Inflammatory and Wound Healing Response of Mesenchymal Stem Cell and Macrophage - Juan Carlos Chachques; Chiara Gardin; Nermine Lila; Letizia Ferroni; Veronique Migonney; Celine Falentin-Daudre; Federica Zanotti; Martina Trentini; Giulia Brunello; Tiberio Rocca; Vincenzo Gasbarro; Barbara Zavan (Biomedicines, 2021)
A challenge in contractile restoration of myocardial scars is one of the principal aims in cardiovascular surgery. Recently, a new potent biological tool used within healing processes is represented by exosomes derived from mesenchymal stem cells (MSCs). These cells are the well-known extracellular nanovesicles released from cells to facilitate cell function and communication. In this work, a combination of elastomeric membranes and exosomes was obtained and tested as a bioimplant. Mesenchymal stem cells (MSCs) and macrophages were seeded into the scaffold (polycaprolactone) and filled with exosomes derived from MSCs. Cells were tested for proliferation with an MTT test, and for wound healing properties and macrophage polarization by gene expression. Moreover, morphological analyses of their ability to colonize the scaffolds surfaces have been further evaluated. Results confirm that exosomes were easily entrapped onto the surface of the elastomeric scaffolds, increasing the wound healing properties and collagen type I and vitronectin of the MSC, and improving the M2 phenotype of the macrophages, mainly thanks to the increase in miRNA124 and decrease in miRNA 125. We can conclude that the enrichment of elastomeric scaffolds functionalized with exosomes is as an effective strategy to improve myocardial regeneration.